Kehidupan Berorganisasi dalam Muhammadiyah - Wahyuni, Sri; Salsabila, Ti’laili (CV. Ulil Albab Corp, 2024)
The Muhammadiyah organization is a fairly large organization in Indonesia. Most Indonesians live their lives with the ideology of Muhammadiyah. The purpose of this study is to describe the organizational life in Muhammadiyah. The research method used in this study is library research, by tracing the literature related to the research focus. After the data is collected, then analysis is carried out which is then drawn a conclusion. The result of this study is that the Muhammadiyah Organization is a large Islamic organization in Indonesia. The name of this organization is taken from the name of the Prophet Muhammad SAW, so that Muhammadiyah is known as people who are followers of the Prophet Muhammad SAW. The Islamic life of Muhammadiyah citizens is formed in creed, morals, worship and worldly mu'amalah While in the family is about the position of the family, family functions, and family activities. Community life means establishing brotherhood, having examples, different religions and carrying out congregational movements and congregational da'wah.